Carpal Tunnel Syndrome As a Presenting Feature of Polymyositis: A Case Report From India - Arijit NAG,; Debanjali SINHA,; Sumantro MONDAL,; Atanu CHAKRABORTY,; Alakendu GHOSH2, (Archives of Rheumatology, 2014)
Polymyositis is a subset of idiopathic inflammatory muscle disorders in which clinical spectrum includes involvement of predominantly musculoskeletal system with varying degree of gastrointestinal, pulmonary and cardiac manifestations. Neuropathic presentation is extremely unusual. In this article, we report a very rare case of a 33-year-old female case with polymyositis with bilateral carpal tunnel syndrome.